PFGE analysis of Listeria monocytogenes isolates from milk, bovine clinical and bovine environment origin from Nagpur - Warke, Shubhangi Rambhau; Ingle , Vijay Chokharam; Kurkure, Nitin Vasantrao (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Listeria monocytogenes, a foodborne pathogen, causes  listeriosis, that mainly affects immunocompromised persons. Epidemiological investigation and molecular subtyping can be helpful in linking the specific sources of infection. Thirty-eight isolates of Listeria monocytogenes recovered from the bovine environment, milk, and  bovine clinical cases  were characterized by serotyping and pulse field gel electrophoresis (PFGE) to correlate the genetic links between the isolates. Serotyping revealed 3 L. monocytogenes isolates to be of serovar group 4b, 4d and 4e, 34 isolates of serovar group 1/2b, 4b, 3b, 4d, 4e, and one isolate to be serovar group 1/2a, 1/2c,3a, and 3c. The PFGE analysis revealed 38 L. monocytogenes isolate from seven different clusters combined ApaI and AscI with 80% relative genetic similarity. In comparison majority of the strains showed location and serovar wise homology in PFGE pattern than source wise. It was also observed that at the place of collection, the organisms circulate in the environment. The present findings suggested that the dairy/bovine farm environment is a potential source of contamination of L. monocytogenes in milk and animals.
Keywords: Bovine environment; , L.monocytogenes Pulsed field gel electrophoresis; Serotyping